Women in Paid Employment: A Role for Public Policies and Social Norms in Guatemala - Rita K. Almeida; Mariana Viollaz (Institute of Labor Economics (IZA), 2022)
With only 32% of active age women in the labor market, Guatemala is an upper middle-income country with one of the lowest rates of female labor force participation in the Latin America and the Caribbean region, and in the world. The rate of female labor participation is especially low in the poor regions of the North and the Northwest. We explore information from different micro data sets, including the most recent Population Census (2002 and 2018) to assess the drivers of the recent progress. Between 2002 and 2018, FLFP increased 5.7 percentage points, from an average of 26% to 32% nationwide. This increase was partly explained by the drastic increases in the school attainment of women, the reduction in fertility and the country's structural transformation towards services. However, a large component remains unexplained. Exploring 2018 data, we show that social norms, attitudes towards women in the society and public policies are important determinants of these changes. The analysis suggests that, taken together, these factors can all become an important source of increased female labor force participation moving forward.
Keywords: J16; J21; J22; O12; 330; female labor force participation; gender; Guatemala